1990
DOI: 10.1177/001872679004301002
|View full text |Cite
|
Sign up to set email alerts
|

Transformations of Life Structure and Personal Paradigm During the Midlife Transition

Abstract: In this exploratory study, data were collected from 64 men and women experiencing midlife transitions. Transformations of life structure during the phases of midlife transition were noted. Some changes (degree of conflict, temporariness, and fulfillment potential) were best accounted for by the act of progressing through the steps of this major transition in life; other changes in life structure (complexity, flexibility, and self-determination) were better accounted for by an internal process of paradigm shift… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…The form, based on Levinson's (1978;1986; theory of life structure, was created by the researchers. In addition, questions in similar qualitative studies (Carpenter & Patterson, 2004;Gordon et al, 2002;Rickards, 2005;Robinson & Smith, 2010;Smithson, 2011;Stumpf, 2012;Wolfe et al, 1990) were examined when creating the current form. The first section on the form consists of eight questions about gender, age, profession, etc.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The form, based on Levinson's (1978;1986; theory of life structure, was created by the researchers. In addition, questions in similar qualitative studies (Carpenter & Patterson, 2004;Gordon et al, 2002;Rickards, 2005;Robinson & Smith, 2010;Smithson, 2011;Stumpf, 2012;Wolfe et al, 1990) were examined when creating the current form. The first section on the form consists of eight questions about gender, age, profession, etc.…”
Section: Methodsmentioning
confidence: 99%
“…Carpenter (1992) determined differences based on individual life structure and experiences in defining the leisure time in adulthood. Wolfe, O'Connor, and Crary (1990) found the life structure transformations in a study with 64 males and females in mid-age transition. They revealed that the dimensions of potential realization, degree of conflict, and transience were in a central position.…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…The theories above show that making a sexual preference change requires both a cognitive and a cultural change which includes a shift in previous belief systems. Wolfe, O'Connor, and Crary (1990) found that many people experience a paradigm shift in varying degrees at certain points in their lives. They define "paradigm" as the underlying set of assumptions, feelings, values and expectations that a person holds.…”
Section: The Mid-age As Influenced By Cultural and Social Changesmentioning
confidence: 99%
“…I define a life crisis as a significant event in a woman's life. The crisis could be the impetus for a woman experiencing the paradigm shift that Wolfe, O'Connor and Crary (1990) talked about. In other words, it could be the reason she began to question the direction and flow of her life.…”
Section: Transitional Marker: Life Crisis-death Divorce Trauma Empmentioning
confidence: 99%